แนวทางการปรับใช้ระบบควบคุมโครงการด้วยวิธีกำหนดเวลาการทำงานแบบทำซ้ำในโครงการก่อสร้างถนนของกรมทางหลวง - ปาลวัตร มะลิทอง (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
Construction planning plays an important role in today’s construction in order to monitor, track, and evaluate the construction performance. Recently, Repetitive Scheduling Method (RSM) is developed to consider repetitive activities in the construction planning. The RSM utilize resources and eliminates float in repetitive processes, leads to better cost effective than the ordinary Critical Path Method (CPM). This study adopts the Ethnographic Delphi Futures Research (EDFR) technique to identify pros and cons in applying the RSM for the highway construction under the Department of Highways, Ministry of Transport. Questionnaires are distributed to experts, including project manager, director of planning section, director of road construction section and director of planning and evaluation group. The results show that the RSM helps manage the usage of resources, reducing floats of activities and hence cost-saving benefits. Nevertheless, The RSM is a complicated method. The cost identification is not fully compatible with the standard procurement of Department of Highways (DOH). To implement the RSM in DHO, the staffs should be trained and a commercial RSM software should be developed. Further, efficient coordination between related departments/contractors are necessary to satisfy the RSM main concept of continuous repetitive processes.